PROSES PRODUKSI BAGIAN LINE OTHER DI PT. BINA BUSANA INTERNUSA (BBI) SEMARANG - Hendra Kurniawan; Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2017)
In Production Process, factory machinery and raw materials are an important part to facilitate the production process. One of the factors that affect the smoothness of the production process is the machine. Need care as a thing that should not be missed considering the machine is one of the important organ for the existence of the company. PT. Bina Busana Internusa (BBI) Semarang, is a company engaged in the garment industry that produces fashion and clothing sportswear. Required to improve the quality of products that are generally on the cause are human and machine factors, for human factors needed to increase training, Make the assessment system work, machine operators are more supervised performance in the work while the engine factor needs to be checked the readiness of the machine before and after use to standard operational and perform periodic maintenance of the machine.Key Words: Production, Line Order